U-Shaped Association of Visceral Fat Area With Diabetic Peripheral Neuropathy - Xianhua Li; Yingxiang Wang; Xiaotong Feng; Lin Mao; Jing Ke; Dong Zhao (Journal of Diabetes Research)
Conclusions: A U-shaped association exists between VFA and DPN prevalence in T2DM patients, suggesting clinical relevance of moderate visceral adiposity.